Severe Methemoglobinemia Secondary to Ferula asafoetida Ingestion in an Infant: A Case Report - Al-Qahtani, Saleh (Saudi J Med Med Sci, 2020)
Methemoglobinemia is an increase in the methemoglobin levels in the blood. Infants are more susceptible to develop secondary methemoglobinemia because of the limited activity of methemoglobin reductase B enzyme. We report a case of life-threatening methemoglobinemia secondary to ingestion of Ferula asafoetida herbal remedy in an infant who presented with cyanosis and severe respiratory distress. The patient had two brothers who had a glucose-6-phosphate dehydrogenase deficiency and the patient's deficiency status was unknown, and thus, methylene blue was not initiated whereas ascorbic acid was unavailable. Accordingly, the patient was successfully treated with hyperoxia. Based on this case, the authors suggest that the use of F. asafoetida as an herbal remedy should be avoided in infants, and pediatricians should be aware of such toxicity and inform parents appropriately.